Corporate Board of Directors Structure and Efficiency - Lahlou, Ismail (Springer International Publishing, 2018)
Corporate governance, a subject that a few decades ago escaped the attention of all but a handful of academics and shareholders, has gradually become a central concern worldwide. This book contributes to the existing literature on the structure and effectiveness of corporate boards. It comprises three topics that address distinct research questions on board structure, the deployment of board resources to monitoring and advisory duties, and the use of equity-based incentives in the compensation packages of directors. Firstly, the book provides strong new evidence on the importance of corporate board functions in value creation. Secondly, it provides some evidence of the potential conflict between the two primary functions of corporate boards. The results indicate that while the board's advising quality weakens when the board is principally devoted to monitoring duties, the presence of advisory directors on the board does not have any impact on the effectiveness of board oversight, which offers a more complete view on the tradeoffs between the board's two major functions. Finally, the results suggest that the closer directors' compensation is tied to the firm's stock, the more consistent corporate acquisition decisions are with shareholder interests.